Construction and evaluation of novel αvβ3 integrin ligand-conjugated ultrasmall star polymer micelles targeted glomerular podocytes through GFB permeation. (September 2021) - Huang, Chengyuan; Zhao, Xuan; Su, Meiling; Yin, Zongning
Abstract: As glomerular cells, podocytes are the last line of defense for glomerular filtration barriers (GFB) and play a critical role in chronic kidney disease (CKD). Podocyte-targeted drug delivery is a promising direction in the treatment of CKD. In this study, we constructed four-arm star polymers conjugated with a novel linear RWrNM peptide. And poly ε-caprolactone (PCL) hydrophobic core and brush poly (2-hydroxyethyl methacrylate) (PHEMA) hydrophilic shell were synthesized by ROP and SET LRP polymerization. The PHEMA modified by succinic anhydride was coupled with the novel linear RWrNM peptide, and then the PCL hydrophobic core was loaded with dexamethasone acetate (Dexac) to form micelles with stable dimensions. Our findings showed that the novel micelles had an ultrasmall particle size of 16–30 nm. We, for the first time, showed that the specific affinity of the novel linear RWrNM peptide to primary podocytes (24.9 ± 1.7 times of the free RhB uptake) through the αvβ3 integrin receptor mediation was comparable to that of B16F10 cells (24.4 ± 1.2 times of the free RhB uptake). In vivo studies showed that the novel ultrasmall micelles possessed a significant kidney-targeted effect, excellent podocyte colocalization effect, and GFB permeability at 49%–60 % in normal SD rats. Besides, the novel ultrasmall micelles decreased the plasma elimination half-life of Dexac to 1.62–2.09 h and showed good safety in vitro and in vivo. Both in vitro and in vivo results demonstrated the novel ultrasmall micelles could be used as a promising drug delivery strategy for actively targeted therapy of CKD. Highlights: Novel ultrasmall drug-loaded micelles with a size of 16–30 nm. First confirmed, RWrNM peptide, high affinity to podocytes, comparable to B16F10. Significant kidney-targeted and podocyte-colocalization, high GFB permeability. The ultrasmall drug-loaded targeted micelles had good safety in vitro/vivo.